2015
DOI: 10.1155/2015/843721
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Treatment Attenuates Pulmonary Inflammatory Cytokine Release and Tissue Injury following Intestinal Ischemia Reperfusion Injury in Mice

Abstract: Objective. Intestinal ischemia reperfusion (II/R) injury plays a critical role in remote organ dysfunction, such as lung injury, which is associated with nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway. In the present study, we tested whether ginsenoside Rb1 attenuated II/R induced lung injury by Nrf2/HO-1 pathway. Methods. II/R injury was induced in male C57BL/6J mice by 45 min of superior mesenteric artery (SMA) occlusion followed by 2 hours of reperfusion. Ginsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…The loss of antioxidant enzymes evidently causes free radical accumulation and further aggravates lung I/R injury [31, 32]. Interestingly, a previous study reported the antioxidative activity of MaR 1 in CCl4-induced liver injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of antioxidant enzymes evidently causes free radical accumulation and further aggravates lung I/R injury [31, 32]. Interestingly, a previous study reported the antioxidative activity of MaR 1 in CCl4-induced liver injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular superoxide anions can oxidize hydroxylamine, resulting in nitrite which shows purplish red under the action of chromogenic agent. The samples in all groups were added to 96-well plates and measured with commercial assay kits for SOD (Nanjing Jiancheng Bioengineering Institute, A001-01, Nanjing, China) and for MDA ((Nanjing Jiancheng Bioengineering Institute, A003-04, Nanjing, China), respectively as described [23]. …”
Section: Methodsmentioning
confidence: 99%
“…To date, several ginsenosides, including Rb1, Rg3, Rg1, Rd, Rh1, and 20( S )‐protopanaxatriol, were found to activate the Nrf2 pathway, whereas Rg3 was also shown to inhibit the Nrf2 pathway (Fig. ).…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 99%